Metabolic vulnerability of cancer stem cells and their niche - Marrone, Laura; Romano, Simona; Malasomma, Chiara; Di Giacomo, Valeria; Cerullo, Andrea; Abate, Rosetta; Vecchione, Marialuisa Alessandra; Fratantonio, Deborah; Romano, Maria Fiammetta (Frontiers in Pharmacology, 2024)
Cancer stem cells (CSC) are the leading cause of the failure of anti-tumor treatments. These aggressive cancer cells are preserved and sustained by adjacent cells forming a specialized microenvironment, termed niche, among which tumor-associated macrophages (TAMs) are critical players. The cycle of tricarboxylic acids, fatty acid oxidation path, and electron transport chain have been proven to play central roles in the development and maintenance of CSCs and TAMs. By improving their oxidative metabolism, cancer cells are able to extract more energy from nutrients, which allows them to survive in nutritionally defective environments. Because mitochondria are crucial bioenergetic hubs and sites of these metabolic pathways, major hopes are posed for drugs targeting mitochondria. A wide range of medications targeting mitochondria, electron transport chain complexes, or oxidative enzymes are currently investigated in phase 1 and phase 2 clinical trials against hard-to-treat tumors. This review article aims to highlight recent literature on the metabolic adaptations of CSCs and their supporting macrophages. A focus is provided on the resistance and dormancy behaviors that give CSCs a selection advantage and quiescence capacity in particularly hostile microenvironments and the role of TAMs in supporting these attitudes. The article also describes medicaments that have demonstrated a robust ability to disrupt core oxidative metabolism in preclinical cancer studies and are currently being tested in clinical trials.